Sistematični pregled literature - Rozman, Urša (Sodobna pedagogika, 2025)
Many studies are showing the benefits of social and emotional learning. The review of studies also reveals shortcomings in researching, comparing and reviewing research in this area. Measurements in this field are not consistent, nor do they have the same long tradition. The literature shows that social and emotional learning has been measured for three decades in the United States, whereas in Europe it has only been measured in the last decade and on a much smaller scale. In this review, we have limited ourselves to meta-analyses and systematic studies in the field of social and emotional learning. We also note the lack of systematic studies on social and emotional learning in the Slovenian context. In order to highlight such research, which allows us to review the effectiveness of social and emotional learning programmes, we have searched the Web of Science, Psycarticles and Scopus databases. The final analysis included 24 studies in the field of social and emotional learning, which systematically show the type of review of each study, the number of studies included in each review, as well as the effects and findings of the programmes. For the purpose of this article, we formulated two research questions: 1) what do systematic reviews and meta-analyses show in terms of countries of implementation, samples and research focus, and 2) what are the effects and findings of individual studies. This was done to show the extent of the research on social and emotional learning and to address the dilemmas that arise in research. The findings show that social and emotional learning programmes have a positive impact on students and also later in life, and that there are different types of social and emotional learning programmes. Despite the variety of programmes, research on the effects of social and emotional learning is shown to be necessary, as it helps to better implement the programmes in school systems and to select among the different programmes those that show effects.
Keywords: sistematični pregled literature; socialne in čustvene kompetence; socialno in čustveno učenje; učinki